2010
DOI: 10.1097/aln.0b013e3181cea398
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Inhibition at the Glycine Site of the N -Methyl-d-Aspartate Receptor Mediates Xenon Neuroprotection against Hypoxia–Ischemia

Abstract: We show that xenon neuroprotection against hypoxia- ischemia can be reversed by increasing the glycine concentration. This is consistent with competitive inhibition by xenon at the NMDA receptor glycine site, playing a significant role in xenon neuroprotection. This finding may have important implications for xenon's clinical use as an anesthetic and neuroprotectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 46 publications
4
71
0
4
Order By: Relevance
“…Since the discovery that xenon was an NMDA receptor antagonist [24] and the subsequent demonstration that xenon has neuroprotective properties in models of ischemic injury [25][26][27][28][29][30][31][32][33][34] there has been a resurgence of interest in the use of xenon as a neuroprotectant. Clinical trials are currently evaluating xenon in different types of ischemic injury (e.g.…”
Section: Clinical Relevance Of These Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery that xenon was an NMDA receptor antagonist [24] and the subsequent demonstration that xenon has neuroprotective properties in models of ischemic injury [25][26][27][28][29][30][31][32][33][34] there has been a resurgence of interest in the use of xenon as a neuroprotectant. Clinical trials are currently evaluating xenon in different types of ischemic injury (e.g.…”
Section: Clinical Relevance Of These Findingsmentioning
confidence: 99%
“…Following the discovery that xenon is an NMDA receptor antagonist [21][22][23][24], xenon was shown to be neuroprotective in a number of in vitro and in vivo models of ischemic injury [25][26][27][28][29][30][31][32][33][34] and xenon is currently undergoing clinical trials as a treatment for ischemic brain injury [35,36] and post-operative delirum [37].…”
Section: Introductionmentioning
confidence: 99%
“…Malfunction of the SH3 domain has a significant impact on such important processes as p53-mediated apoptosis and DNA repair (Jiang et al 2001), adhesion-dependent regulation by tyrosine phosphorylation (Moore and Winder 2010), stimulation of mesenchymal stem cell migration, which is important for hypoxic solid tumor development (ProulxBonneau et al 2011), osteoblast maturation and consequently bone formation (Levaot et al 2011), the assembly of amyloid fibrils and determination of their morphology (Morel et al 2010), processes associated with a number of neurodegenerative diseases, such as Alzeimer's (Morel et al 2010), tyrosine phosphatase signaling that affects SH3 binding in patients with rheumatoid arthritis (Bilwes et al 1999), bacteria adhering to host cells (Queval et al 2011) and contraction-induced injuries (Banks et al 2010). Mutations in the SH3 domain of unconventional myosin VIIa have recently been shown to cause deafness in humans, with one mutation, A1628S, located directly in its SH3 domain (Wu et al 2011).…”
Section: Regulationmentioning
confidence: 99%
“…The inert anesthetic gas xenon has received increasing interest as a neuroprotectant over the last decade. Xenon has proven to be neuroprotective both in vivo and in vitro with minimal adverse effects (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). We and others have previously reported that adding immediate xenon to HT enhanced the neuroprotective effects of HT after induced hypoxia-ischemia in neonatal rats (12,13,15,20) and newborn pigs (21).…”
mentioning
confidence: 99%